2003
DOI: 10.1097/00000478-200303000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Mammary Carcinoma After Immediate and Short-Term Follow-up for Lobular Neoplasia on Core Biopsy

Abstract: Lobular neoplasia (LN), including atypical lobular hyperplasia (ALH) and lobular carcinoma in situ, may be encountered in breast core biopsies performed for mammographic abnormalities even though LN is often not, in itself, responsible for the abnormal mammogram. The need for surgical excision following a diagnosis of LN on core biopsy is not well defined. We examined pathologic and mammographic findings in a consecutive series of cases diagnosed as LN to address this issue. Radiology/pathology records were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Colocalization of calcifications with lesions was observed in 28% of cases in the LN group and 37% of cases in the ADH group. This relatively high rate of colocalization in the former group (which encompasses classic LCIS and ALH), in agreement with the findings of a previous study, 32 should prompt a reevaluation of the traditional view that LN is not associated with radiographically detectable abnormalities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Colocalization of calcifications with lesions was observed in 28% of cases in the LN group and 37% of cases in the ADH group. This relatively high rate of colocalization in the former group (which encompasses classic LCIS and ALH), in agreement with the findings of a previous study, 32 should prompt a reevaluation of the traditional view that LN is not associated with radiographically detectable abnormalities.…”
Section: Discussionsupporting
confidence: 90%
“…32,35 Conventional wisdom holds that LN is an incidental finding in areas adjacent to benign, mammographically detected calcifications and that calcifications are only rarely associated with LN. 24 Carson et al 36 found calcifications in association with LCIS in 21% of mammographically detected lesions (4 of 19), and Crisi et al 32 reported colocalization of calcifications with LN in 41% of cases (12 of 29). In the current study, calcification was the initial mammographic abnormality that prompted core biopsy in 67% of cases in the LN group, compared with 80% of cases in the ADH group.…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency of finding calcifications present within LCIS/ALH in needle core biopsy samples ranges from 8% to 41%. 6,7,9,18,25,31,32 In our series, we found calcifications to be present within LCIS in a significant percentage of cases (38 of 61; 62%), and that frequency was even higher among cases specifically targeting calcifications (36 of 50; 72%). Calcifications were present exclusively in LCIS in 10 of 61 cases (16%), and that finding was slightly more frequent among cases targeted for calcifications (10 of 50; 20%).…”
Section: Commentsupporting
confidence: 47%
“…The number of cases included in previously published studies (combining atypical lobular hyperplasia and lobular carcinoma in situ) varies from less than 10 up to 92 cases of lobular neoplasia followed by immediate excision. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In comparison, our study includes a relatively high number of cases (87 cases of lobular neoplasia followed by immediate excision). Another limitation in our study and others is that it is retrospective and may suffer from selection bias regarding the patients that underwent excision.…”
Section: Discussionmentioning
confidence: 99%